Tech noir: Aesthetic connections between burroughs’ naked lunch and contemporary extreme metal - Mackenzie, J.A. (Intellect Ltd., 2018)
William S. Burroughs remains a shadowy presence in the history of metal music. But the connections that have been forged between the author and metal generally relate to the influence he has had upon the lexicon and themes of the genre. This article moves away from the issue of influence and argues that Burroughs’ radical literary style is analogous to contemporary extreme metal genres such as mathcore, which blend metal and punk. Both mathcore and Burroughs’ Naked Lunch employ structural unpredictability and rapid shifts in pace. But rather than simply disrupting the social order, these startling aesthetic strategies can be understood as representations of the contemporary world, which can encourage audiences to adapt to and retain agency within the chaos of postmodernity. The first steps are also taken in this article to assemble a genealogy of works that produce such empowering effects. © 2018 Intellect Ltd Article.
Keywords: Burroughs; Death Metal; Extreme Metal; Grindcore; Mathcore; Naked Lunch; Speed Postmodernism